EFFECT OF TRIDAX PROCUMBENS HYDROETHANOLIC EXTRACT ON WISTAR RATS BLOOD GLUCOSE, TOTAL CHOLESTEROL, AND TRIGLYCERIDES - MEDEGAN, SÈDAMI (My University, 2016)
The hypoglycemic, hypotensive and antioxidant effects of Tridax procumbens have been fundamentally studied in India where the plant is widely used for its medicinal properties. In this work, we treated Wistar rats with two doses of leaves and stems hydroethanolic extract of Benin species of Tridax procumbens every day for 15 days. Three groups of 5 rats were formed, the first control group was treated with 1 ml of water every day, the second group was treated with 1ml of 300mg / kg body weight of extract and the third group was treated with a dose of 500mg / kg body weight every day. Histological studies of the liver and kidney of untreated and treated animals was made to check the toxicity of the extract. Our results demonstrated after 15 days of treatment that none of the doses used has a significant effect on rat blood sugar however we observed a dose dependent effect on lowering blood cholesterol levels compared to controls and a decrease of blood triglycerides levels by the dose of 300mg / kg body weight compared to controls. The two doses used were not toxic to the liver or the kidneys. Tridax procumbens hydroethanolic extract through its regulation of lipid levels in the blood of Wistar rats could fight against dyslipidemia in obese, added to its antioxidant activity the extract could prevent type II diabetes and cardiovascular diseases
Keywords: Tridax procumbens-Wistar rats-cholesterol-triglycerides